Analgesic and antiinflammatory activities of the aqueous root extract of Algerian Bunium incrassatum - Amraoui, Nacer; Boutefaha, Zineddine; Belattar, Noureddine; Arrar, Lekhmici (Archives of Biological Sciences, 2024)
Paper description: Bunium incrassatum, commonly known as Black Cumin, is a plant that has been traditionally used in various cultures for culinary and medicinal purposes. The in vitro antioxidant and in vivo analgesic and anti-inflammatory activities of the aqueous extract from the roots of B. incrassatum were examined in mice. The aqueous extract of B. incrassatum exhibited in vivo anti-inflammatory activity in xylene- and Croton oil-induced ear edema, carrageenan-induced paw edema, and analgesic activity in acetic acid writhing and formalin paw-licking experimental models. B. incrassatum can be an effective source of compounds with antioxidant, anti-inflammatory, and analgesic effects. Abstract: The present study was designed to evaluate the antioxidant, analgesic, and antiinflammatory activities of Bunium incrassatum aqueous extract (BIAE) from roots. Tests of radical scavenging of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and induced erythrocyte hemolysis using 2,2′-azo bis (2-amidinopropane) dihydrochloride (AAPH) were used for antioxidant activity evaluation. The antiinflammatory activity was tested in Croton oil- and xylene-induced ear edema and carrageenan-induced paw edema. The antinociceptive effect was tested with the pain model induced by formalin and acetic acid-induced writhing response. The results revealed that BIAE exhibited a strong protective effect against AAPH-induced hemolysis of erythrocytes. In contrast, in the DPPH test, BIAE showed moderate activity (IC50: 1.07±0.078 mg/mL) compared to BHT. In the antiinflammatory test, oral administration of BIAE (100, 300, and 600 mg/kg) significantly reduced the edema in the three models used. In antinociceptive experiments, the pretreatment with BIAE produced important analgesic activity. Additionally, the pretreatment of mice with BIAE significantly reduced the paw-licking time in the second phase. The results of this study revealed the antioxidant, analgesic, and antiinflammatory potential of BIAE, and demonstrated the importance of B. incrassatum as a source of compounds for therapeutic uses.